1975
DOI: 10.1002/pen.760150210
|View full text |Cite
|
Sign up to set email alerts
|

The thermal conductivity of nickel and copper dispersed in poly(vinyl chloride)

Abstract: The thermal conductivity of segregated distributions of poly (vinyl chloride)/nickel (PVC/Ni) and poly(vinyl chloride)/copper (PVC/Cu) was measured for volume fractions ranging from 0 to 0.15. The thermal conductivities increased from 0.15 Btu/hr ft °F for unmodified PVC to 2.79 Btu/hr ft °F for PVC/15 percent Cu. While the thermal conductivity increased smoothly with volume loading, the electrical resistivity decreased discontinuously over fifteen orders of magnitude. Using the parallel slab model as a basis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Another common segregated system involves the use of polymer powder mixed with conductive filler and then pressed at a temperature near the melting point of the polymer. [26][27][28][29] These powder-based composites have percolation thresholds that are higher than for blends (4-6 vol.-%), but maximum conductivity is similar.…”
Section: Introductionmentioning
confidence: 99%
“…Another common segregated system involves the use of polymer powder mixed with conductive filler and then pressed at a temperature near the melting point of the polymer. [26][27][28][29] These powder-based composites have percolation thresholds that are higher than for blends (4-6 vol.-%), but maximum conductivity is similar.…”
Section: Introductionmentioning
confidence: 99%
“…Mamunya stated that previous modelling work [18][19][20][21] showed an absence of percolation behaviour, and the lack of thermal percolation threshold is due to the thermal conduction properties of the matrix where the polymer will have its own thermal conductivity regardless of filler content. Also, previous work conducted to account for the additional thermal conductivity 22,23 did not take into account a realistic filler geometry connected to the packing factor.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…Thus, in ref. (Kusy and Corneliussen, 1975) it has been found that thermal conductivity in polyvinyl chloride/copper (PVC/Cu) segregated composites more than twice the value was achieved over epoxy/metal composites with only a fraction of loading. The power-law equation, describing the concentration dependence of PVC/Ni segregated system, contains the variable value of exponent in opposite to usual form of this equation with constant value of exponent in case of random filler distribution (Mamunya et al, 2002c).…”
Section: Development Of the Segregated System Approachesmentioning
confidence: 99%
“…From this point of view ultrahigh molecular weight polyethylene (UHMWPE) is a preferred matrix (Zhang et al, 2005). Since first detailed study of Malliaris & Turner, 1971 many investigations of segregated systems based on metal (and ceramic) particles as conductive filler were fulfilled, for example (Boushet et al, 2000;Bridget et al, 1990;Kusy, 1977;Kusy & Corneliussen, 1975;Lebovka et al, 2006;Mamunya et al, 2002bMamunya et al, , 2002cPrivalko et al, 2000;Yacubowicz et al, 1990b). Extensive study of segregated polymer/metal systems and their possible applications were presented elsewhere (Kusy, 1986) where the prominent achievements in this area have been summarized.…”
Section: Development Of the Segregated System Approachesmentioning
confidence: 99%
See 1 more Smart Citation